The moment of embalming: T. S. Eliot's love letters - a report from the archive - Sullivan, H (Times Newspapers Ltd., 2020)
Discusses T. S. Eliot's love letters to Emily Hale. This infamous archive was unsealed at Princeton University Library in January 2020.